2014
DOI: 10.1016/j.cub.2014.03.073
|View full text |Cite
|
Sign up to set email alerts
|

The Right Dorsal Habenula Limits Attraction to an Odor in Zebrafish

Abstract: These data provide physiological and functional evidence that the habenula functions as a higher center in zebrafish olfaction and suggest that activity in the right dorsal subdomain gates innate attraction to specific odors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 35 publications
(55 reference statements)
4
100
0
Order By: Relevance
“…The natural log fold change in fluorescence was fit to a normal distribution and the mean and standard deviation determined. Neurons were deemed responsive if the change in fluorescence intensity post-shock was greater than 1 standard deviation of the mean [52, 53], and responsive neurons on average had a greater than 2-fold increase in neural activity [54]. The initial time point at which neuronal activity increased, for a given neuron, was determined using the MATLAB function ‘ findpeaks ’.…”
Section: Star ★ Methodsmentioning
confidence: 99%
“…The natural log fold change in fluorescence was fit to a normal distribution and the mean and standard deviation determined. Neurons were deemed responsive if the change in fluorescence intensity post-shock was greater than 1 standard deviation of the mean [52, 53], and responsive neurons on average had a greater than 2-fold increase in neural activity [54]. The initial time point at which neuronal activity increased, for a given neuron, was determined using the MATLAB function ‘ findpeaks ’.…”
Section: Star ★ Methodsmentioning
confidence: 99%
“…2(b')]. Clusters of activity could be found in the olfactory bulb (OB) and habenula (Hb), the latter considered to be involved in relaying odorevoked behavioral responses, 19,20 as well as in some neurons of the optic tectum (OT) [Figs. 2(b)-2(c)].…”
Section: Resultsmentioning
confidence: 99%
“…We stimulated the larvae with the odorant cadaverine (Cad, 10-μM solution), a diamine generated by decarboxylation of the amino acid lysine during decomposition of flesh, which is known to evoke olfactory-related neural activity and avoidance responses in zebrafish larvae. 19,20 Figure 2 shows three image planes through the volumetrically reconstructed light field dataset [ Fig. 2(a)], as well as a top-down maximum intensity projection [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cells that can be identified based on morphology, location, or functional characteristics, can be targeted for ablations using high-power, pulsed lasers. For instance, single neuron ablations in the reticulospinal system have been used to identify the reticulospinal neurons necessary for certain defined types of swim (Liu and Fetcho, 1999;Orger et al, 2008;Kohashi and Oda, 2008;Huang et al, 2013), or even particular kinematic parameters of individual swim bouts (Severi et al, 2014;Thiele et al, 2014), and similar methods have also been used to generate lesions in more broadly defined areas (Roeser and Baier, 2003;Mu et al, 2012;Krishnan et al, 2014). A particularly powerful approach is to combine genetic specificity with the spatial control of optical methods, for example, using the phototoxic protein KillerRed (Lee et al, 2010).…”
Section: Many Transgenic Lines Exist Which Allow Expression Of Genes mentioning
confidence: 98%
“…Krishnan et al developed a simple, wide-field epifluorescence system for rapid three-dimensional imaging using fast focusing and deconvolution, and applied this method to reveal, with single cell resolution, the dynamics in response to different concentrations of multiple odors throughout the whole habenula (Krishnan et al, 2014). They found that population activity in the right dorsal habenula varied with the concentration of a socially relevant odor (a bile salt), and provided evidence, using pharmacology and ablations, that this region mediates a switch from attraction to avoidance at high concentrations.…”
Section: Comprehensive Imaging From Neural Populationsmentioning
confidence: 99%